Peningkatan Hasil Belajar Siswa dalam Pembelajaran IPS Menggunakan Model Snowball Throwing di Sekolah Dasar - hakim, hazizul; S, Farida; Lubis, Mansur (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2019)
The purpose of the study to describe the increase in student learning outcomes in learning IPS by using the model of Snowball Throwing in class V SDN 29 Ulak Karang Padang City academic year 2017/2018. The type of research is PTK in learning IPS class  V  SDN  29  Ulak  Karang  Padang  City.  Research  subjects  were  teachers  and students of class V. There were 26 students consisting of 12 female students and 14 male students. The results showed, Snowball Throwing model can improve student learning outcomes in IPS learning in class V SDN 29 Ulak Karang Kota Padang. Based on the average class of 77.4 cycles I meeting I and 82.2 cycles I meeting II, thus the average cycle I is 79.83. In the second cycle obtained an average of 96.3. Keywords: Snowball Throwing, learning outcomes